(untitled) (Journal of Education and Development, 2022)
The vocational education has a long history and has developed into a relatively complete legal protection system. In particular, since 1984, the United States has adopted the vocational education act as the basis, after a series of reforms in vocational education, the Perkins Act is typical in the history of American vocational education, and it is the epitome of the development of vocational education. This paper begins with the Carl D Perkins Act of 1984, analyzes the background of the act, probes into the many forces and organizations promoting the Act, and analyzes the main contents and purposes of the act, further discussion on the impact of the Perkins Act on American vocational education will provide some reference for better understanding the vocational education.